Three-dimensional representation of the human cochlea using micro-computed tomography data: Presenting an anatomical model for further numerical calculations. - Braun, Katharina; Böhnke, Frank; Stark, Thomas (Acta Oto-Laryngologica, 2012)
Conclusion: We present a complete geometric model of the human cochlea, including the segmentation and reconstruction of the fluid-filled chambers scala tympani and scala vestibuli, the lamina spiralis ossea and the vibrating structure (cochlear partition). Objective: Future fluid-structure coupled simulations require a reliable geometric model of the cochlea. The aim of this study was to present an anatomical model of the human cochlea, which can be used for further numerical calculations. Methods: Using high resolution micro-computed tomography (µCT), we obtained images of a cut human temporal bone with a spatial resolution of 5.9 µm. Images were manually segmented to obtain the three-dimensional reconstruction of the cochlea. Results: Due to the high resolution of the µCT data, a detailed examination of the geometry of the twisted cochlear partition near the oval and the round window as well as the precise illustration of the helicotrema was possible. After reconstruction of the lamina spiralis ossea, the cochlear partition and the curved geometry of the scala vestibuli and the scala tympani were presented. The obtained data sets were exported as standard lithography (stl) files. These files represented a complete framework for future numerical simulations of mechanical (acoustic) wave propagation on the cochlear partition in the form of mathematical mechanical cochlea models. Additional quantitative information concerning heights, lengths and volumes of the scalae was found and compared with previous results.